2022
DOI: 10.3390/ijms23073696
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Association Analysis for Carotenoid Content among Sprouts of Cowpea (Vigna unguiculata L. Walp)

Abstract: The development and promotion of biofortified foods plants are a sustainable strategy for supplying essential micronutrients for human health and nutrition. We set out to identify quantitative trait loci (QTL) associated with carotenoid content in cowpea sprouts. The contents of carotenoids, including lutein, zeaxanthin, and β-carotene in sprouts of 125 accessions were quantified via high-performance liquid chromatography. Significant variation existed in the profiles of the different carotenoids. Lutein was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…In comparison to cross-pollinated crops, LD decay was observed to be slower in self-pollinated crops [ 15 , 50 ]. The extent of LD decay in the association panel of chickpea was observed at 200–300 kb [ 51 ] and at 5 cM in chickpea reference set [ 20 ] and for cowpea at 1.4 Mb [ 52 ]. The extent of LD can vary due to the complexity and size of the genome and marker number [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to cross-pollinated crops, LD decay was observed to be slower in self-pollinated crops [ 15 , 50 ]. The extent of LD decay in the association panel of chickpea was observed at 200–300 kb [ 51 ] and at 5 cM in chickpea reference set [ 20 ] and for cowpea at 1.4 Mb [ 52 ]. The extent of LD can vary due to the complexity and size of the genome and marker number [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to TLC, liquid chromatography (LC) helps to achieve both the separation and quantification of specific carotenoids and their isomers. HPLC analyses using C18 and C30 columns as stationary phases have successfully been deployed for carotenoid analysis in cowpea [25,41,54,55]. Ultra-performance liquid chromatography (UPLC) and ultra-high-performance liquid chromatography (UHPLC) are modern LC techniques used for the separation of carotenoids in cowpea [40].…”
Section: Destructive Methods For Quantification Of Carotenoids In Cowpeamentioning
confidence: 99%
“…GWAS was performed to identify loci associated with crops’ nutrient status, enhancing biofortification efforts. In one of these studies, seven loci were identified through GWAS that were associated with the carotenoid content of sprouts of 125 cowpea accessions including landraces [ 92 ]. Moreover, a GWAS was undertaken recently on 161 accessions, including landrace material to identify markers related to cowpea seed protein content, in which three candidate genes were identified [ 93 ].…”
Section: Application Of New Genomic Technologies In Landraces and Ind...mentioning
confidence: 99%